UNRAVELLING THE MYSTERIES OF SPORADIC CJD. Issue 11 (9th October 2013) - Mackay, Graham; Yull, Helen; Ironside, James; Head, Mark; Knight, Richard
Abstract : Introduction: Sporadic CJD is a neurodegenerative illness first described in the 1920s. The condition is postulated to be spread by a process of direct protein to protein transmission. The prion hypothesis suggests that normal cellular proteins (PrPc) convert to an abnormal conformation (PrPSc), which forms a template for further protein misfolding. The variable phenotype of Sporadic CJD (sCJD) is largely felt to depend on a combination of the codon 129 genotype of the prion protein gene (MM, MV or VV) and the presence of the two major conformations of the protease–resistant prion protein (type 1 or type 2) in the brain. Cases were sub–classification on this basis into six discrete subtypes (MM1/MV1, VV1, MM2c, MM2t, MV2, VV2) with each characterised by a different clinico–pathological phenotype (Parchi et al, 1999). Recently a significant minority of patients have been found to have both protein types, challenging this classification system. Methods: PrPres typing was undertaken in 108 pathologically confirmed sporadic CJD patients referred to UK CJD surveillance. This analysis was undertaken in the temporal, parietal and occipital lobes and the thalamus in all patients. A structured assessment of their clinical and pathological features was undertaken. Results: 26 of 108 patients had both type 1 and 2 proteins on western blot analysis. Comparison of the most common mixed group with most common pure group [MM 1(+2) with MM1] showed subtle differences in their clinical phenotypes and investigations patterns. However, the major clinical findings were the same. Differing clinical profiles were seen relative to the ratio of predominant protein type. There were no pathological findings unique to any genotype–isotype group. Conclusions: While there were differing trends, the lack of distinct clinical or pathological findings by sub–type suggest that these groups do not represent unique strains of prions, but rather groupings over a spectrum of disease.